2002
DOI: 10.1046/j.1523-1755.2002.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitor blocks expression of mediators of renal injury in a model of diabetes and hypertension1

Abstract: These results suggest that in an experimental model of diabetes and hypertension, inhibition of COX-2 expression decreases potential mediators of glomerular and tubulointerstitial injury and also decreases biochemical, functional and structural markers of renal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
167
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 65 publications
21
167
1
1
Order By: Relevance
“…Therefore, Celecoxib is not simply blocking the effect of COX-2, but is also perturbing COX-2 protein production; a finding noted in previous studies (Cheng et al, 2002;Agarwal et al, 2003). In COX-2 expressing HT29 colon cancer cell lines, COX-2 inhibition with another selective COX-2 inhibitor SC236 (a structural analogue of Celecoxib) showed that at high levels of inhibitor (concentrations greater than 75 mm), COX-2 enzyme activity was completely inactivated.…”
Section: Celecoxib Decreases Cox-2 Protein Expressionmentioning
confidence: 68%
“…Therefore, Celecoxib is not simply blocking the effect of COX-2, but is also perturbing COX-2 protein production; a finding noted in previous studies (Cheng et al, 2002;Agarwal et al, 2003). In COX-2 expressing HT29 colon cancer cell lines, COX-2 inhibition with another selective COX-2 inhibitor SC236 (a structural analogue of Celecoxib) showed that at high levels of inhibitor (concentrations greater than 75 mm), COX-2 enzyme activity was completely inactivated.…”
Section: Celecoxib Decreases Cox-2 Protein Expressionmentioning
confidence: 68%
“…COX metabolites have been implicated in the renal damage that occurs in animal models and patients with metabolic syndrome [58][59][60][61][62]. There are at least two COX enzymes, COX-1 and COX-2, expressed in the kidney.…”
Section: Eicosanoids As a Therapeutic Target For Renal Damage In Cardmentioning
confidence: 99%
“…There are at least two COX enzymes, COX-1 and COX-2, expressed in the kidney. COX metabolites play a critical role in renal blood flow regulation, renin generation and vascular inflammation [25,58,63]. Alterations in COX metabolites contribute to endothelial dysfunction and renal damage in diabetes [56,64,65].…”
Section: Eicosanoids As a Therapeutic Target For Renal Damage In Cardmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al 33 showed that p38 in macula densa cells is involved in regulation of cyclooxygenase-2 (COX-2) under certain conditions, such as low chloride tubular content. Since COX-2-derived metabolites have been implicated in the pathophysiology of progressive renal disease, including diabetes, 34,35 this is an attractive pathway that may link p38 with the development of nephropathy in diabetes. Interestingly, p38 localization in diabetic rats was almost identical to that of COX-2, as observed in our previous studies.…”
Section: Renal P38 In Experimental Diabetesmentioning
confidence: 99%